Relationship of Glycosylated Hemoglobin with Fasting and Postprandial Plasma Glucose in Nondiabetic, Pre-diabetic and Newly Diagnosed Diabetic Subjects - Saiedullah, M; Begum, S; Shermin, S; Rahman, MR; Khan, MAH (Bangladesh Medical Journal, 2012)
Glycosylated hemoglobin (HbA1c) is considered as an index of glycemic status of previous 2 to 3 months. HbA1c in diabetic subjects is translated to average glucose (eAG) and well correlated to mean plasma glucose (MPG). This study was performed to assess the relationship of fasting plasma glucose (FPG) and postprandial plasma glucose (PPG) with HbA1c in nondiabetic, pre-diabetic and newly diagnosed diabetic subjects. Seven hundred subjects of both sexes were included conveniently in this study. Fasting and 2 hours postprandial plasma glucose concentrations were measured by hexokinase method. HbA1c was measured by high performance liquid chromatyography (HPLC) based hemoglobin assay system. Subjects were classified into three groups according to WHO criteria. The correlation coefficient between FPG and HbA1c were 0.2495 (P<0.001), 0.2665 (P<0.001) and 0.8010 (P<0.001) in the nondiabetic, pre-diabetic and newly diagnosed diabetic subjects respectively. The correlation coefficient between PPG and HbA1c were -0.0661 (P>0.05), 0.2447 (P<0.01) and 0.7812 (P<0.001) in the nondiabetic, pre-diabetic and newly diagnosed diabetic subjects respectively. This study revealed that fasting plasma glucose had a modest higher relation with HbA1c than 2 hours postprandial plasma glucose in the newly diagnosed diabetic subjects. It can be concluded that evaluation of FPG may provide better outcome than PPG in the newly diagnosed never treated diabetic subjects. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9961 BMJ 2011; 40(1): 37-38